O controle prévio dos editais de licitação pelos Tribunais de Contas - Lima, Guilherme Corona Rodrigues (2015)
This work has as goal the analysis of control by the Courts of Accounts in the previous control performed face of bidding documents. Therefore the constitutional and legal competence of the Courts Accounts and particularly the control of the bidding activity of public administration were analyzed, detailing the Court of Auditors s jurisdiction. Finally, we sought to determine the criteria and limits for both as well as the procedure to be observed in exercising such control, seeking in doctrine and jurisprudence parameters for both